2015
DOI: 10.1056/nejmp1508037
|View full text |Cite
|
Sign up to set email alerts
|

Maryland's Global Hospital Budgets — Preliminary Results from an All-Payer Model

Abstract: In the first year of Maryland's experiment in setting all-payer rates for hospital services, costs were contained and the quality of care improved, though the state still has high rates of hospital admissions and per capita spending for Medicare patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 4 publications
0
43
0
Order By: Relevance
“…These reforms leveraged the state's preexisting unique all‐payer hospital rate‐setting system and the federal government's State Innovation Models (SIM) Initiative . Previous studies have shown little early impact on inpatient readmission rates in TPR's rural hospitals and on either potentially preventable complications or inpatient utilization after GBR's statewide expansion . (See Appendix for more details.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These reforms leveraged the state's preexisting unique all‐payer hospital rate‐setting system and the federal government's State Innovation Models (SIM) Initiative . Previous studies have shown little early impact on inpatient readmission rates in TPR's rural hospitals and on either potentially preventable complications or inpatient utilization after GBR's statewide expansion . (See Appendix for more details.…”
Section: Introductionmentioning
confidence: 99%
“…7 Previous studies have shown little early impact on inpatient readmission rates in TPR's rural hospitals 8 and on either potentially preventable complications or inpatient utilization after GBR's statewide expansion. [9][10][11][12] (See Appendix S1 for more details. )…”
mentioning
confidence: 99%
“…In the first year alone, Maryland saved Medicare $116 million while reducing the rate of potentially preventable conditions by 26.3%. 19 In Rhode Island, a policy change created a mandated increase in primary care expenditures to 10% of total health care expenditures, leading to a savings of over $100 million in its first 4 years. 20 Rather than simply increasing fee-forservice rates for primary care services, payers were required to instead invest in other primary care There is currently no streamlined, organized system of payment for healthcare.…”
Section: ) Payment: Breaking Down Vertical Silos Of Care Creating Gmentioning
confidence: 99%
“…More specifically, the case demonstrates how a calculative tool (hospital budgeting) facilitates the aims of reducing utilisation and costs while motivating both cooperation and quality improvement. In 2014, the US state of Maryland applied the “Global Budget” approach to implement extensive changes in hospital treatment practices (Patel et al., ). The policy aimed to replace a volume‐based reimbursement system with a global budget, with the twin goals of improving the quality of healthcare and controlling costs (Evans & Meyer, ; Patel et al., ) .…”
Section: Introductionmentioning
confidence: 99%
“…In 2014, the US state of Maryland applied the “Global Budget” approach to implement extensive changes in hospital treatment practices (Patel et al., ). The policy aimed to replace a volume‐based reimbursement system with a global budget, with the twin goals of improving the quality of healthcare and controlling costs (Evans & Meyer, ; Patel et al., ) . The global budget in Maryland represents an unconventional shift in behavioural motivations towards quality of care, moving away from the traditional focus on volume.…”
Section: Introductionmentioning
confidence: 99%